Visceral Adiposity, Inflammation, and Testosterone Predict Skeletal Muscle Mitochondrial Mass and Activity in Chronic Spinal Cord Injury - Goldsmith, Jacob A.; Lai, Raymond E.; Garten, Ryan S.; Chen, Qun; Lesnefsky, Edward J.; Perera, Robert A.; Gorgey, Ashraf S. (Frontiers in Physiology, 2022)
Background: Mitochondrial health is an important predictor of several comorbidities including obesity, type 2 diabetes mellitus, and cardiovascular disease. In persons with spinal cord injury (SCI), mitochondrial health has been linked to several important body composition and metabolic parameters. However, the complex interplay of how mitochondrial health is affected has yet to be determined in this population. Objective: In this study, we examined the contribution of visceral adiposity, inflammatory biomarkers, testosterone and circulating serum growth factors as predictors of mitochondrial health in persons with chronic SCI. Participants: Thirty-three individuals with chronic SCI (n = 27 Males, n = 6 Females, age: 4013.26 years, level of injury: C4-L1, BMI: 235.57) participated in this cross-sectional study. Methods: Visceral adipose tissue (VAT) was measured via magnetic resonance imaging (MRI). After an overnight fast, serum testosterone, inflammatory biomarkers (interleukin 6 [IL-6], tumor necrosis factor alpha [TNF-], c-reactive protein [CRP]), and anabolic growth factors (insulin-like growth factor 1 [IGF-1], insulin-like growth factor binding protein 3 [IGFBP-3]) were measured. Skeletal muscle biopsies were obtained from the vastus lateralis muscle to measure citrate synthase (CS) and Complex III activity. Regression analyses were used to examine predictors of mitochondrial mass and activity. Results: CS activity was negatively associated with VAT (r2=.360, p<.001), CRP (r2=.168, p=.047), and positively associated with testosterone (r2=.145, p=.042). Complex III activity was negatively associated with VAT relative to total lean mass (VAT:TLM) (r2=.169, p=.033), trended for CRP (r2=.142, p=.069), and positively associated with testosterone (r2=.224, p=.010). Multiple regression showed CS activity was significantly associated with VAT+CRP (r2=.412, p=.008) and VAT+Testosterone (r2=.433, p=.001). Complex III activity was significantly associated with VAT relative to total trunk cross-sectional area (CSA)+CRP (VAT:total trunk CSA+CRP; r2=.286, p=.048) and VAT+Testosterone (r2=.277, p=.024). Conclusions: Increased visceral adiposity and associated inflammatory signaling (CRP) along with reduced testosterone levels predict mitochondrial dysfunction following SCI. Specifically, lower VATCSA and higher testosterone levels or lower VATCSA and lower CRP levels positively predict mitochondrial mass and enzyme activity in persons with chronic SCI. Future research should investigate the efficacy of diet, exercise, and potentially testosterone replacement therapy on enhancing mitochondrial health in chronic SCI.